Pedological analysis and statistical variation of mapping soil unit of Greater Mussiab Project / Babylon Province - Abdul - Ameer, Hameed K. (Journal of Kerbala for Agricultural Sciences, 2017)
Soil survey map at series level of greater mussiab project 35 km north Babylon Province between 32˚ 32' - 32˚ 47' N and 44˚ 29' - 44˚ 55' E used to analysis pedologicaly to limit the state of soil series and their relation between them .Three soil series wich various in physiographic region was choose to determine the statistical variation of soil particle to study the sedimentological environment and characteristic of region sedimentology. Results show 18 soil series various in frequency and their area , MM11 series was the greatest area and frequency , pedological distribution of texture was 35.02% to moderately coarse textured , 39.22% to moderately textured and 25.53% to fine textured , the result also show strong relationship between irrigation levee and river basin physiographic unit because both contain the same soil series , particles analysis appear medium and fine silt was over all average fraction . In mean time sediment exhibited poor sorting , positive skewness coefficient showed smooth surface due to abrasion fluvial transport and sediment as well as kurtosis coefficient appear.